The Incidence and Management of Urethral Stricture in Bladder Carcinoma - Reyad Ahmed Farhood; Othman Jasim Mohammed Alzaidy; Aiad Abd Al Hameed Hassen (Diyala Journal of Medicine, 2021)
Background: Urethral stricture disease is one of the oldest and most difficult maladies known to the urologist. While references  to the disease and its treatment date back to the writings of the Hindus, Egyptians, and Greeks.